The Legal Politics of the Enforcement of Constitutional Court Decisions in Indonesia: Politik Hukum Eksekusi Putusan Mahkamah Konstitusi Di Indonesia - Christia, Adissya Mega; Wardhani, Lidya Christina; Tristy, Marsatana Tartila; Surya, Faizal Adi (Universitas Islam Indonesia, 2024)
The Constitutional Court is the only state institution that can carry out constitutional review of regulations and the result is expressed through a decision. The decision of the Constitutional Court is final and binding and at that time the principle of erga omnes applies where the legal force of the Constitutional Court's decision applies to anyone, not just limited to the parties involved in the case. This research aims to analyze the legal politics of 4 (four) Constitutional Court Decisions based on their nature and principles and shows their urgency. The approach method used is normative juridical with descriptive analysis. The results of this research are that the legal politics of executing Constitutional Court decisions has not yet been implemented because in reality there are still situations where decisions are not in harmony with statutory regulations, returning to statutory regulations before amendments, not followed by new and complicated statutory regulations. to be implemented. The legal political urgency of executing Constitutional Court decisions must return to the principle of final and binding nature as well as the principle of erga omnes, one of which is through ab initio confirmation if the decision is not complied with by other state institutions.Keywords: Constitutional Court, Constitutional Court Decision, Political Law AbstrakMahkamah Konstitusi adalah satu-satunya lembaga negara yang dapat melakukan uji konstitusional terhadap undang-undang dan hasilnya dinyatakan melalui putusan. Putusan Mahkamah Konstitusi bersifat final dan mengikat (binding) serta pada saat itu pula berlaku asas erga omnes di mana kekuatan hukum Putusan Mahkamah Konstitusi berlaku pada siapa saja, tidak hanya terbatas berlaku bagi para pihak yang berperkara. Penelitian ini bertujuan menganalisis politik hukum dari 4 (empat) Putusan Mahkamah Konstitusi berdasarkan sifat dan asas serta menunjukkan urgensinya. Metode pendekatan yang digunakan adalah yuridis normatif dengan analisis deskriptif. Hasil dari penelitian ini adalah politik hukum eksekusi Putusan Mahkamah Konstitusi belum berjalan sebab pada kenyataannya masih terdapat keadaan di mana putusan tidak harmonis dengan peraturan perundang-undangan, kembali pada peraturan perundang-undangan sebelum amandemen, tidak diikuti oleh peraturan perundang-undangan yang baru dan rumit untuk dilaksanakan. Urgensi politik hukum eksekusi Putusan Mahkamah Konstitusi harus kembali kepada prinsip sifat final dan mengikat (binding) serta asas erga omnes salah satunya melalui penegasan ab initio apabila putusan tidak dipatuhi oleh pihak lembaga negara lain.Kata Kunci: Mahkamah Konstitusi, Politik Hukum, Putusan Mahkamah Konstitusi